A importancia do desenvolvimento da competência em informação no contexto de clubes de futebol - Jorge, Carlos Francisco Bitencourt [UNESP]; Valentim, Marta Lígia Pomim [UNESP] (My University, 2017)
Information is one of the implicit components in different organizational processes, so it is necessary that the organizational individuals are granted the competences to provide the best use of data and information. Observing the environment in which soccer clubs are inserted it is possible to note the use of data and information all the time, and most of the time, being used as a strategic resource. From this perspective, it analyzes the perception, access, sharing and use of data and information aligned with information literacy on the Marilia Athletic Club, of Marilia City, in Sao Paulo State. For this, we used a qualitative research, applying the direct observation method for collecting and analyzing data. From the analysis was possible to notice how organizational individuals use information and highlighted the importance of the information literacy development, so that they can perform their roles, responsibilities and tasks undertaken in the Club. It also evidenced distinct information needs regarding the use of data and information, confirming that the information literacy development on the soccer club's context is essential, after all, everyone involved in the Club have information needs and therefore need to develop skills aimed at better use of information.
The importance of information literacy development on soccer clubs context
Keywords: Information literacy; Information management; Soccer clubs; Sportive information; Sports environments